1988
DOI: 10.1007/bf02898321
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sulfur contents of vegetable and marine oils by ion chromatography and indirect ultraviolet photometry of their combustion products

Abstract: A simple method for the determination of total sulfur content in vegetable and marine oils is described. The method involves combustion of the oil sample in an oxygen bomb to convert all forms of sulfur to sulfate ions with subsequent determination of the sulfate by ion chromatography and indirect ultraviolet detection. The ultraviolet system described is more sensitive than conductivity detection and enables the method to be applied more widely.Application of the method to a variety of vegetable and marine oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Vegetable oil in the Cruciferae family such as rapeseed and canola oils are known to contain sulfur (S) compounds [3], which are powerfully poisonous to the catalysts. However, the work carried out on S tolerance of the catalyst particularly for partial hydrogenation of polyunsaturated FAME has not been done.…”
Section: Dear Sirmentioning
confidence: 99%
“…Vegetable oil in the Cruciferae family such as rapeseed and canola oils are known to contain sulfur (S) compounds [3], which are powerfully poisonous to the catalysts. However, the work carried out on S tolerance of the catalyst particularly for partial hydrogenation of polyunsaturated FAME has not been done.…”
Section: Dear Sirmentioning
confidence: 99%
“…Ion chromatography coupled with indirect UV detection is a convenient method for quantitative analysis of anions (2). Under the conditions used in this study chloride, nitrite, nitrate, sulfate and selenate ions were well separated from each other ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Initially, triacetin was tested according to the previous procedure (2), in which sample degassing was not carried out and no oxygen-filled glove-bag was used. Surprisingly, the combustion products contained nitrite as well as Figs.…”
Section: Resultsmentioning
confidence: 99%
“…However, trace amounts of enzymatic hydrolysis products of glucosinolates are still present in canola oil . Daun and Hougen showed that crude oil can contain about 10–50 mg kg −1 sulfur, which is mostly removed during conventional refining process to 9 mg kg −1 or less . These organic compounds can poison the catalysts applied for hydrogenation and give the characteristic odor to the oil.…”
Section: Reduction In Antinutritive Compoundsmentioning
confidence: 99%
“…[94] Daun and Hougen [95] showed that crude oil can contain about 10-50 mg kg À1 sulfur, which is mostly removed during conventional refining process to 9 mg kg À1 or less. [96] These organic compounds can poison the catalysts applied for hydrogenation and give the characteristic odor to the oil. Simultaneously, sulfur components may increase stability of the oil acting as antioxidants.…”
Section: Glucosinolates (Gsls)mentioning
confidence: 99%